Trajectoires paysagères et crises morphosédimentaires de cônes torrentiels dans la vallée de la Maurienne (Savoie) depuis la fin du Petit Âge glaciaire - Thérèse Hugerot; Laurent Astrade; Christophe Gauchon (Projets de Paysage)
To reconstruct the geohistorical dynamics of mountain environments the places that are most likely to record natural and anthropogenic changes need to be identified. Four torrential cones were chosen in the Maurienne Valley (in the Northern French Alps) because of the diversity of the land uses and landscapes they represent. The use of numerous cadastral, cartographic, photographic and technical archives from between the 18th and 20th centuries has enabled the creation of a geohistorical information system capable of describing and characterising the landscape trajectories of these four cones since the Little Ice Age. The frequency of torrential activity and morphosedimentary crises, the industrialisation of the valley and its rural decline, major road, rail and hydroelectric developments, and the dynamics of urbanisation (and post-war reconstruction) are all factors to be taken into account in reconstructing these unique trajectories. In addition to the specific features of the four cones studied, six major phases in the evolution of the landscape have been identified which alternate between periods of damage caused by debris flows and periods of calm. The current situation is characterised by the spread of fallow land on the cones and the artificialisation of the torrent banks.